GOOGLE MEET APPLICATION AS A TEACHING LEARNING PROCESS MEDIA : (A Case study students and lecturers in Institut Agama Islam Ngawi ) - Imam wahyudi (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
ABSTRACT: This study investigates Google Meet application to be used as a teaching learning process in Institute Agama Islam Ngawi, the research design of this study qualitative approach and the research was A case study. The participants of the study were lecturers and students in Institut Agama Islam Ngawi. The result of this study Google Meet could be used as alternative media to teaching learning process during pandemic Covid - 19 although it was going quite difficult because the tools were not prepared and checked.